Dysregulation of ubiquitination modification in renal cell carcinoma - You, Hongjie; Zhang, Hui; Jin, Xiaofeng; Yan, Zejun (Frontiers in Genetics, 2024)
Renal cell carcinoma (RCC) is a malignant tumor of the renal tubular epithelial cells with a relatively high incidence rate worldwide. A large number of studies have indicated that dysregulation of the ubiquitination, including ubiquitination and dysregulation, is associated with the occurrence and development of RCC. This review focuses on several abnormal signaling pathways caused by E3 ligases and deubiquitinases. Additionally, we discuss research progress in RCC treatment by targeting key enzymes related to ubiquitination modifications.